Integrating Perplexity AI into Academic Research: A Study on Research Gap Analysis and Proposal Development - Dio Manik; Yeni Adventry Tanjung; Rita Hartati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study examines how Perplexity AI is integrated into academic research, particularly its role in research gap analysis and proposal development among university students. Using a qualitative descriptive method and questionnaire data from 32 participants, the research explores students’ perceptions, benefits, and ethical considerations regarding AI- assisted research. The findings reveal that Perplexity AI improves efficiency in literature review and research gap identification, with 75% of students using it to explore research topics and 65.6% acknowledging its usefulness in recognizing trends and gaps. However, concerns remain about accuracy and source reliability, as only 56.3% fully trust AI-generated results, and many still verify information manually. The study concludes that effective use of Perplexity AI requires strong AI literacy that includes critical thinking, verification skills, and ethical awareness. These insights contribute to a broader understanding of human–AI collaboration in academic settings and highlight the need for responsible, well-guided integration of AI tools in research education.